(untitled) (Journal of Musikot Campus, 2024)
This research is regarding to the analysis of results of five community schools of 2076 to 2080 B.S. in Rukum West District. Research has focused on student performance in Nepali, English, Mathematics, and Social Studies. The objectives cover evaluating the pass rates of basic level students, classifying achievement rates, and recognition reasons for low academic achievement with suggestions for improvement. The quantitative research approach and secondary data were used for the study. The finding reveals significant insights into the educational performance of students. The overall pass rate fluctuated over the five years, with an average pass percentage of 90.13%. The highest pass rate was recorded in 2076, and the lowest in 2078. Subject-wise analysis showed that Mathematics consistently had the lowest pass rates compared to Nepali, English, and Social Studies. This trend continued across the years, highlighting the need for targeted interventions in Mathematics education.